2016
DOI: 10.1155/2016/4950576
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Thermal Conductivity of Composite Materials (CPC-30R/Charcoal from Sugarcane Bagasse) Using the Hot Insulated Plate Technique

Abstract: The production of new thermally insulating composite materials from solid residues such as charcoal from sugarcane bagasse (CSB) is of great importance because it takes advantage of materials that might otherwise pollute the environment. Therefore, for this study, we obtained composite materials based on a portland cement (CPC-30R) matrix and CSB particles with a 4 : 1 water-cement ratio and CSB concentrations of 5%, 10%, and 15% by weight. The thermal conductivities of these materials were characterized follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…The EPS showed an increase in TC values, indicating that it had less resistance to heat transmission. A decrease in the TC value of SBFs indicates a higher resistance to transmission of heat through the material . In general, it was observed that the TC values from PF (9 g) and EPS were statistically different (α = 0.05).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The EPS showed an increase in TC values, indicating that it had less resistance to heat transmission. A decrease in the TC value of SBFs indicates a higher resistance to transmission of heat through the material . In general, it was observed that the TC values from PF (9 g) and EPS were statistically different (α = 0.05).…”
Section: Resultsmentioning
confidence: 94%
“…The thermal conductivity (TC) of SBF was measured following the method of Salgado‐Delgado et al . A hot plate system based on the ASTM guideline C177–97 (Standard Test Method for Steady State Heat Flux Measurements and Thermal Transmission Properties by Means of the Guarded Hot Plate Apparatus) was used.…”
Section: Methodsmentioning
confidence: 99%
“…6 , 27 , 28 Thus, nonwovens with lignocellulosic hemp fibers have high efficiency as heat-insulating materials. 29 The thermal conductivity values obtained for all nonwovens were in the range 0.027–0.034 W/(m K) range. These values were even lower than those of traditional thermal insulation materials.…”
Section: Resultsmentioning
confidence: 91%
“…Depending on the material's microstructure, it can be either thermally conductive or insulating. Considering Fourier's law of conduction, it is stated that heat conduction happens when there is a temperature differential between two bodies and following Equation () 20 : Kgoodbreak=goodbreak−Q×LA×T where K is the thermal conductivity (W/m°C), Q is the heat flow (W), L is the thickness of the sample (m), Δ𝑇 is the temperature difference (°C), and 𝐴 is the area of the sample that perpendicular to the direction of heat (m 2 ).…”
Section: Methodsmentioning
confidence: 99%